ANCA-negative EGPA: only eosinophils without vasculitis? Insights from anti-T2 biologics - Piga, Mario Andrea; Fraticelli, Paolo; Antonicelli, Leonardo; Garritani, Maria Stella; Ghirelli, Giulia; Martini, Matteo; Di Vincenzo, Angelica; Danieli, Maria Giovanna; Moroncini, Gianluca; Bilò, Maria Beatrice (Frontiers in Immunology, 2023)
The pathogenic role of p-ANCA in eosinophilic granulomatosis with polyangiitis (EGPA) is a longstanding matter of debate. In this work, we report our real-life experience with EGPA patients, treated with biologics targeting type 2 (T2)-eosinophilic inflammation (Mepolizumab, Benralizumab, Dupilumab). Interestingly, we observed EGPA extrarespiratory relapses only in p-ANCA-positive patients (2/5 cutaneous vasculitis, 3/5 constitutional symptoms), with new rise of p-ANCA and normal eosinophil blood count. Notably, revising our cohort with the new ACR 2022 criteria, these five patients were the only ones to satisfy the entry criterion of vasculitis' defined diagnosis at disease onset. These observations may suggest that biologics, selectively turning off T2 inflammation, may have unmasked p-ANCA exclusive role in the pathogenesis of vasculitis in EGPA. Therefore, we raise the question whether EGPA vasculitis exists only in p-ANCA-positive patients, and whether p-ANCAnegative disease is "only eosinophils without vasculitis".